Moderating role of perceived benefit between sustainable environmental manufacturing practices and firm performance - Adebambo, Hameed O.; Ashari, Hasbullah; Nordin, Norani (Penerbit UTM Press, 2015)
The need to maintain a balance between the developmental and environmental issues in manufacturing firms is required to ensure that the cost of environmental changes does not negate the economic benefits perceived by the firms.Therefore, this study investigated the effect of sustainable environmental manufacturing practices on firm performance via the moderating effect of perceived benefits.The study used a survey questionnaire which was posted to the operation, manufacturing manager and the environmental, health and safety manager to collect 103 data from the Malaysian manufacturing firms.The data collected was analyzed with smartPLS 2. M3.The study found that sustainable environmental manufacturing practices significantly influence environmental performance, while perceived benefits moderates between sustainable environmental manufacturing practices and operational performance. The study has revealed the understanding of the scenario of sustainable manufacturing practices in a developing country as yet to be considered as a strategic factor.Therefore, it is suggested that more awareness should be created to enlighten the manufacturing practitioners not only to perceive sustainable environmental practices as ethical, but also as a strategic factor to enhance achieving better firm performance.